Black artists of the Harlem Renaissance in western survey textbooks: Narratives of omission and representation. Issue 3 (1st September 2013) - Grant, Alphonso Walter; Kee, Jessica Baker
In this article we examine the inclusion of Black American artists in a selection of western survey art history textbooks using the Harlem Renaissance as an analytical exemplar. We first examine Black intellectual and artistic representations of the Great Migration and the Harlem Renaissance arguing that this work provides a vital contribution to the Western Modernist art tradition. We argue that although there is a great deal of critical contemporary scholarship around the Harlem Renaissance period, three problematic narratives still persist in college-level textbooks: the omission of Black American artists from the larger narrative of Modernist art, the misrepresentation of major themes of Harlem Renaissance art, and a continued focus on Modernist tropes of primitivism. We analyse the content of three mainstream western art history textbooks using Kymberly Pinder's (1999) theory of the 'native informant' as well as other major ideas surrounding Black visual omission and representation. Finally, we examine possible implications of these problematic narratives for art educators, students and historians.